2014
DOI: 10.1002/jts.21879
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Perceived Social Reactions to Trauma‐Related Experiences With PTSD and Depression Among Veterans Seeking PTSD Treatment

Abstract: The Social Acknowledgment Questionnaire (SAQ; Maercker & Mueller, ) is a measure of trauma survivors' perceptions of social acknowledgment and disapproval from others, and these factors are shown to be associated with posttraumatic stress disorder (PTSD) among civilian trauma survivors. This study seeks to validate the structure of the SAQ among U.S. military veterans and test the hypothesis that family and general disapproval are associated with PTSD and depression among veterans. Participants were 198 U.S. v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 34 publications
4
25
2
Order By: Relevance
“…In our study, only general disapproval-not family disapproval-was positively related to PTSD. This pattern has been shown before (Schumm et al, 2014), but the reasons for these findings are not yet well understood. Ullman and Filipas (2001) suggested that different origins of acknowledgment may become more or less important according to an individual's cultural background, sex, or type of traumatic experience.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, only general disapproval-not family disapproval-was positively related to PTSD. This pattern has been shown before (Schumm et al, 2014), but the reasons for these findings are not yet well understood. Ullman and Filipas (2001) suggested that different origins of acknowledgment may become more or less important according to an individual's cultural background, sex, or type of traumatic experience.…”
Section: Discussionmentioning
confidence: 67%
“…Schumm et al (2014), who performed structural equation modelling of the results of their study of US military veterans seeking PTSD treatment, found that General Disapproval was positively and significantly related to PTSD, whereas both Recognition and Family Disapproval were not. The results of their study also showed that General Disapproval was the only SAQ factor that was significantly related to both PTSD and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in Germany, Ingushetia, China and the USA has proven that social acknowledgement is negatively correlated with PTSD symptoms (e.g. Maercker & Müller, 2004; Maercker, Povilonyte, Lianova, & Pöhlmann, 2009; Mueller, Orth, Wang, & Maercker, 2009; Schumm, Koucky & Bartel, 2014). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively speaking, trauma victims may either experience support from their close surroundings or negative reactions toward their experiences such as being ignored or even blamed for the trauma. Several studies have shown that social acknowledgment is negatively associated with PTSD symptoms among various populations posttrauma (e.g., Maercker and Müller, 2004;Mueller et al, 2009), a trend that is most apparent among war survivors (Schumm et al, 2014).…”
Section: Introductionmentioning
confidence: 99%